2020
DOI: 10.1136/bmjmilitary-2020-001417
|View full text |Cite
|
Sign up to set email alerts
|

Determining the psychophysiological responses of military aircrew when exposed to acute disorientation stimuli

Abstract: IntroductionExposure to enviromental flight conditions may impair performance and physical integrity, thus training in simulated environments it is a key factor. This research aimed to study the psychophysiological response, cortical arousal and autonomic modulation of pilots and medical aircrew personnel during disorientation exposure, considering gender, experience, flying hours and body mass index (BMI) as influencial variables.MethodsA total of 47 soldiers (37 men and 10 women, 22 medical aircrew personnel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Hypothetically, these results could also be explained since all the analysed pilots were expert. A previous study reinforces this explanation since lower HRV values were related to a lower level of experience [ 20 ]. Authors explained that this could be an adaptive response to this stressful environment [ 20 ].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Hypothetically, these results could also be explained since all the analysed pilots were expert. A previous study reinforces this explanation since lower HRV values were related to a lower level of experience [ 20 ]. Authors explained that this could be an adaptive response to this stressful environment [ 20 ].…”
Section: Discussionsupporting
confidence: 75%
“…A previous study reinforces this explanation since lower HRV values were related to a lower level of experience [20]. Authors explained that this could be an adaptive response to this stressful environment [20]. Another study showed that a pilot's first flight was the most stressful [7,39].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The large demand of the intervention, the lack of control, and the uncertainty produce the increase in the stress response through the increase in sympathetic modulation, affecting performance, reducing cardiopulmonary capacity and strength, and momentarily stopping the urine and intestinal processes in order to prioritize organic resources to maintain survival [1,3,7,10,11,14,29]. Specifically in the low-altitude flight, we found an increased anxiety response, probably related with the danger of the maneuver, since it was conducted at a low altitude, and any minimal failure could finish in a mortal accident; nevertheless, during the flight, the sympathetic modulation decreased, showing the habituation expected from highly trained subjects [16]. This response is in line with results obtained in armies and militaries in different combat maneuvers (asymmetrical, symmetrical, urban combat, etc.…”
Section: Discussionmentioning
confidence: 63%
“…Military air operations are considered some of the most stressful events in the military, but most previous aircrew research in this area has been carried out on special tactical groups, such as paratroopers, showing how the exposure to these extreme environments and types of jumps produced a decrease in cortical arousal and an increase in the physiological stress response, mediated by the autonomous sympathetic system [8][9][10][11]. In particular, aircrews are susceptible to suffering a large variety of critical situations, since they are exposed to stressors such as hypoxia, disorientation, G forces, accidents, or air attacks during their interventions, and have to face different demands, such as different types of parachute jumps, nocturnal jumps, ground training in war zones, and different types of flights at different heights-HALO (high altitude low opening) and HAHO (high altitude high opening)-as well as underwater training in case of aircraft accidents between others [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%